PELATIHAN PENULISAN KARYA ILMIAH BIDANG SOSIAL ( HUKUM ) DI SMA NEGERI 3 DENPASAR - SUDIARTA, I KETUT; DHARMAWAN, NK SUPASTI; ARYAN, NYOMAN MAS (Buletin Udayana Mengabdi, 2012)
ABSRACT Training of Constructing Scientific Report on Social Major (Law) has done on SMA Negeri 3 Denpasar, by the Guiding Team of the Lecturers of Law Faculty of Udayana University through a practice of constructing a report in a class through a workshop. Aproximately, 40% are for meanwhile, 60% are by practice of composing and providing some reference which is related to the constructing of a social-scientific report, and there all are done well so far. This fact was indicated by the responds which were given by the students of SMA Negeri 3 Denpasar, especially for those who join the KIR group.This activity has been done once a week.